MULTIPLIER EFFECT PENGELOLAAN WAKAF TUNAI DAN PENGARUHNYA TERHADAP PEMBERDAYAAN UMKM - Izzun Khoirun Nissa; Roby Kurniadinata; Rahid Kurnia (JASIE, 2024)
Based on simple simulations, with various relaxations in economic assumptions, it is proven that cash waqf is capable of providing a fairly large multiplier effect in the economy, whether the results of the cash waqf investment are provided in the form of assistance to the economic sector or the non-economic sector. This will directly and indirectly be able to have a significant influence in alleviating poverty. Apart from that, Micro, Small and Medium Enterprises (MSMEs) can be a force in alleviating poverty, creating jobs and becoming a force in alleviating poverty, creating jobs and being a force in increasing family income.  Cash waqf plays a strategic role in empowering Micro, Small and Medium Enterprises (MSMEs). Cash waqf offers the opportunity to help business groups increase income from the profits they receive. Furthermore, of course this income has a positive impact on changes in the family's economy. Moreover, the investment in waqf funds distributed is provided in the form of revolving funds which are used as business capital for other communities on an ongoing basis.